Association of a Common Polymorphism in the Factor XIII Gene with Myocardial Infarction - Kohler, Hans P.; Stickland, Max H.; Ossei-Gerning, Nicholas; Carter, Angela; Mikkola, Hanna; Grant, Peter J. (Thrombosis and Haemostasis, 1998)
Factor XIII when activated by thrombin, crosslinks fibrin, however its role in thrombotic disorders is unknown. A common point mutation (G T) in exon 2 of the A-subunit gene which codes for an amino acid change three amino acids from the thrombin activation site (Factor XIIIVal34Leu) is a candidate for a role in the pathogenesis of acute myocardial infarction. Factor XIII genotype frequencies were determined in a case-control study of 398 caucasian patients and 196 healthy controls. Patients had undergone angiography for investigation of coronary artery disease and were evaluated for a history of myocardial infarction. The prevalence of the mutation was lower in patients with myocardial infarction than without (32% vs. 50%), p = 0.0009 and than in controls (32% vs. 48%), p = 0.005. Patients possessing the mutation with a history of myocardial infarction had higher PAI-1 concentrations (mean, 27.9 vs. 16.7 ng/ml, p = 0.004) and the PAI-1 4G/4G genotype was commoner (43% vs. 26%, p = 0.03). There was no difference in PAI-1 4G/4G genotype (33% vs. 32%) and PAI-1 levels (mean, 21.0 vs. 20.9 ng/ml) in patients possessing wild type with MI compared to those without MI. These results indicate that the G T mutation coding for factor XIIIVal34Leu is protective against myocardial infarction and suggest a mechanism whereby elevated levels of PAI-1 may contribute to vascular risk.